The State and Indicators of Cytokines in Pregnant Women with Threatened Preterm Labor and Preterm Labor (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Currently, the immunological aspects of preterm birth are being widely studied. According to many studies, the modified immunoreactivity of the maternal organism, including cytokine regulation, is one of the links in the pathogenesis of miscarriage.In modern obstetrics, one of the urgent problems is spontaneous abortion in the period of 22-37 weeks. In this connection, the scientific research of new markers of immune disorders of fetal predictors remains an urgent promising program of modern obstetrics in order to reduce perinatal losses.In accordance with the purpose and objectives of this study, we studied the course of pregnancy and childbirth in 200 women at a gestational age of 22-36 weeks. The main group consisted of 65 women with a threatened miscarriage, 40 women with preterm labor without amniotic fluid and 45 women with amniotic fluid, the control group consisted of 50 women with a physiological course of pregnancy.Immunological studies were carried out in the immunological laboratory of the Specialized Research Republican Center for Obstetrics and Gynecology, senior researcher, Ph.D. Fayzyrakhmonova M.M. Interleukins IL1β, TNF-α, IL1 in the blood plasma of patients were examined using the enzyme immunoassay analyzer Mindray MR-96A.